2016
DOI: 10.1186/s12877-016-0225-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of multicomponent tools designed to assess frailty in older adults: A systematic review

Abstract: BackgroundFrailty is widely recognised as a distinct multifactorial clinical syndrome that implies vulnerability. The links between frailty and adverse outcomes such as death and institutionalisation have been widely evidenced. There is currently no gold standard frailty assessment tool; optimizing the assessment of frailty in older people therefore remains a research priority. The objective of this systematic review is to identify existing multi-component frailty assessment tools that were specifically develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
171
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(187 citation statements)
references
References 96 publications
(461 reference statements)
4
171
0
12
Order By: Relevance
“…Nevertheless, we had to impute data about fatigue for centenarians living in Sweden where the questions about fatigue were not included in the questionnaire. The choice of the frailty phenotype itself could be discussed in the absence of information about the psychometric properties or predictive accuracy of the frailty phenotype among centenarians [33]. This study enabled us to explore demographic, health, and functional factors associated with frailty.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Nevertheless, we had to impute data about fatigue for centenarians living in Sweden where the questions about fatigue were not included in the questionnaire. The choice of the frailty phenotype itself could be discussed in the absence of information about the psychometric properties or predictive accuracy of the frailty phenotype among centenarians [33]. This study enabled us to explore demographic, health, and functional factors associated with frailty.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…There is no universally accepted definition [4,5], but experts agree that it is a clinical syndrome characterised by increased vulnerability and diminished resistance to stressors that can cause functional impairment and increase risks [6,7]; a minor stress or event such as an accidental fall or infection can worsen a person's health condition and increase dependency and/or mortality. Box 2.1 captures the main concepts in definitions of frailty.…”
Section: Frailtymentioning
confidence: 99%
“…28 However, there is still no consensus regarding the conceptual and operational definition of frailty. [29][30][31] Fundamentally, frailty is a medical concept, and as a result, it is often defined in the context of problems in physical functioning. An example of such a definition is the one produced by Fried et al 23 These researchers define frailty as a "biologic syndrome of decreased reserve and resistance to stressors, resulting from cumulative declines across multiple physiologic systems, causing vulnerability to adverse outcomes."…”
Section: Frailty Definitions and Measuresmentioning
confidence: 99%
“…A definition of frailty that expresses this integrative approach is as follows: "Frailty is a dynamic state affecting an individual who experiences losses in one or more domains of human functioning (physical, psychological, social), which is caused by the influence of a range of variables and which increases the risk of adverse outcomes." 33 Recently, Sutton et al 29 identified 38 multi-component frailty measures. One of these measures is the frequently used and cited Frailty Index developed by Mitnitski et al 35 The Frailty Index is based on the cumulative deficit approach and proposes that frailty can be assessed by evaluating a large number of non-specified age-associated health deficits, usually at least 30.…”
Section: Frailty Definitions and Measuresmentioning
confidence: 99%
See 1 more Smart Citation